ANALISIS TEKNIK PENGAMBILAN GAMBAR DAN TEKNIK VOICE OVER PADA VIDEO PROFILE DEVELOPMENT AND ASSESSMENT (CDA) IPB UNIVERSITY - Pranata, Rici Tri Harpin; Rahayu, Alma; Pebrianti, Nispia (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
Profile videos are an effective promotional medium for introducing an organization or institution to the broader community. Shooting and voice-over techniques are important in conveying messages and creating visual appeal when making profile videos. This study analyses the shooting and voice-over techniques used in the CDA IPB profile video. The method in the research used is qualitative descriptive analysis with a case study approach. Data were produced through video observation and voice-over transcripts. The study results show that the CDA IPB profile video uses various shooting techniques such as bird’s eye view, low angle, high angle, frog eye, and eye level techniques. The shooting also considers the size of the image, such as close-up, full shot, knee shot, mid shot, long shot, and extreme long shot. The voice-over technique used in the CDA IPB profile video is the deep voice technique. Using appropriate shooting and voice-over techniques can create an engaging, informative, and compelling profile video that conveys messages to the audience.